Portal Vein Thrombosis in Liver Cirrhosis. Part 2: Treatment, Primary and Secondary Prevention - A. V. Yagoda; P. V. Koroy; L. S. Baisaeva; T. R. Dudov (SINAPS LLC, 2024)
In most cases, portal vein thrombosis progresses without treatment; spontaneous recanalization of portal vein develops in 42 % of patients with liver cirrhosis. Effective treatment strategies include administration of anticoagulants, interventional procedures such as transjugular intrahepatic porto-systemic shunt or endovascular fibrinolysis. Anticoagulant therapy has certain difficulties in patients with liver cirrhosis due to the complex profile of hemostasis, a tendency to both hemorrhages and hypercoagulation. In addition to traditional anticoagulants (heparin preparations, fondaparinux, vitamin K antagonists), direct oral anticoagulants have been widely used in recent years for portal vein thrombosis. Previously, portal vein thrombosis was considered a contraindication to performing transjugular intrahepatic porto-systemic shunt, currently the method is often used to restore portal blood flow through the shunt and prevent repeated thrombosis. Endovascular fibrinolysis is still an option for specialized centers for «difficult» patients. In cases of increased risk of venous thromboembolism, patients with liver cirrhosis are recommended to be prevented with low-molecular-weight heparin or direct oral anticoagulants, but further studies should clarify their effectiveness in this aspect. The review highlights data on the features of therapy, primary and secondary prevention of portal vein thrombosis in patients with liver cirrhosis. Despite the existing clinical recommendations for management of patients with cirrhotic portal vein thrombosis, the choice of a particular strategy primarily depends on an individualized assessment of risks and benefits of each treatment method.